Modeling of Laser-Assisted Cutting of Thin-Walled Steel Gears - Abbos Elmanov; Sirojiddin Kengboyev; Nazirjon Safarov; Adham Norkobilov (Proceedings)
The article provides information on the theoretical foundations, technological processes, and equipment used for the laser cutting of gears from thin-walled (4–10 mm thick) steel, which has received the widest industrial application of all laser processing technologies [...]